ENGLISH WRITING PERFORMANCE USING BLENDED LEARNING IN TVET EDUCATION - Ayuni Madarina Abdul Rahman (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
This study focuses on Technical and Vocational Education and Training (TVET) includes formal, non-formal and informal learning that prepare young people with the knowledge and skills required in the world of work. English has become an important language in Malaysian higher learning institutions that is used as a medium of interaction and for other educational purposes. For this study, the researcher would like to highlight the impacts of blended learning on students’ writing performance. This is due to the concerns regarding students’ difficulty in English writing. The study used experimental research design to conduct the study that involved 60 students from semester 1 who took Communicative English 1. The study has been conducted on two groups, which were experimental and control group. The students had to answer the questionnaire regarding teacher centred approach (control group) and blended learning approach (experimental group). Also, students do writing test to be correlated with the result from questionnaire. SPSS version 23 that used Kendall’s correlation has become the the tool to analyse the result. The result shows that blended learning has a positive effect to the most students in experimental group.